Pembinaan Keluarga Sakinah Melalui Pendekatan Dakwah Di Nagari Batang Arah Tapan - Roshan Zunil Pratama; Ahmad Khairul Nuzuli; Winda Oktavia (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Creating a Sakinah Mawaddah and Warohmah family is the dream of every human being. How happy we are to have a family filled with mutual love, affection, protection and respect. But it turns out that creating a family like that is not a flip of the palm. It requires hard work and support from all parties in the family, including father, mother and children. The aim of this activity is to develop the Nagari Batang Arah Tapan Community into a Sakinah Family through a da'wah approach.